2010
DOI: 10.3109/07853890.2010.521765
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to wartime stress – long-term effect on coronary heart disease in later life

Abstract: Background. Increased rates of coronary heart disease (CHD) and cerebrovascular disease in later life have been repeatedly observed in subjects with low birth-weight. One possible reason for low birth-weight is prenatal stress. Little is known about the influence of prenatal stress on lifelong health outcomes. Aims. In this study we investigate the influence of prenatal stress on CHD and cerebrovascular disease incidence in adult life. Methods. We analysed data originating from the Helsinki Birth Cohort Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The Dutch Hunger Winter study showed increased risks of coronary heart disease, hypertension, as well as type 2 diabetes in later life, while in the two other studies there were no associations found between malnutrition and cardiovascular disease or glucose intolerance. In our previous study of the effects of the bombings of Helsinki during World War II on subjects exposed while in utero, we observed slightly lower rates of both coronary heart disease and cerebrovascular disease in women, suggesting the effect of such a stress to be selective for developing these diseases if anything (4). In conclusion, the hardships of the war were multiple and their effect very hard to estimate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Dutch Hunger Winter study showed increased risks of coronary heart disease, hypertension, as well as type 2 diabetes in later life, while in the two other studies there were no associations found between malnutrition and cardiovascular disease or glucose intolerance. In our previous study of the effects of the bombings of Helsinki during World War II on subjects exposed while in utero, we observed slightly lower rates of both coronary heart disease and cerebrovascular disease in women, suggesting the effect of such a stress to be selective for developing these diseases if anything (4). In conclusion, the hardships of the war were multiple and their effect very hard to estimate.…”
Section: Discussionmentioning
confidence: 94%
“…Traditionally nutritional status, growth, living conditions and maternal stress have been focused upon (14). Environmental conditions including season and ambient temperature have so far not attracted much attention.…”
mentioning
confidence: 99%
“…Conversely, there was also evidence to suggest no association. Schreier et al found a protective effect from exposure to war and coronary heart disease: exposed women between 63 and 80 years and men between 50 and 54 years of age had higher survival rates than the unexposed (Schreier et al 2011). Other studies of famine found no increase in coronary artery disease (Lumey et al 2012), no effect on blood pressure (Roseboom et al 1999), no increased cardiovascular mortality (Ekamper et al 2015), and a weak but significant increase in hypertension prevalence among the exposed (OR 1.44, 95 % CI 1.04, 2.0) (Stein et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the common linear regression analysis cannot be applied in this case. Incidentally, alike the incidence of coronary heart disease and cerebrovascular disease [17], birth weight does not follow a gaussian (i.e., normal) distribution, but is more likely to follow a Weibull hazard model, as birth weight could be considered the final outcome of the "battle for survival" of the fetus.…”
Section: Lack Of Reporting On Confidence Intervalsmentioning
confidence: 99%